2018
DOI: 10.1093/abm/kay039
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and Inflammatory Responses to Acute Stress in People With Type 2 Diabetes

Abstract: Happier individuals with T2D have lower inflammatory markers before and after acute stress, albeit independent of stress responsivity. Findings could provide a protective physiological pathway linking daily happiness with better health in people with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…The results of this study showed that the happiness of patients with higher education level (“high school or secondary school,” “college,” and “undergraduate and above”) was better than those with lower education level, which was in accordance with the results of Pintaudi et al [ 24 ] and Panagi et al [ 25 ] The former is better than the latter in integrating various information channels and acquiring disease management related knowledge. It is easy to have a higher sense of responsibility in the process of disease management and is handier in dealing with the changes of diabetes and complications.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study showed that the happiness of patients with higher education level (“high school or secondary school,” “college,” and “undergraduate and above”) was better than those with lower education level, which was in accordance with the results of Pintaudi et al [ 24 ] and Panagi et al [ 25 ] The former is better than the latter in integrating various information channels and acquiring disease management related knowledge. It is easy to have a higher sense of responsibility in the process of disease management and is handier in dealing with the changes of diabetes and complications.…”
Section: Discussionsupporting
confidence: 91%
“…Of these, 101 participants had complete information for all IL-6 and IL-1RA measurements, and 102 individuals had full MCP-1 data. The missing data were due to issues in blood sampling as previously reported (Panagi, Poole, Hackett, & Steptoe, 2018). Issues included difficulties maintaining a functioning cannula in obese participants and cannula failure part way through the session.…”
Section: Participant Characteristicsmentioning
confidence: 93%
“…As an example of the potential confluence of stress, food access, and racism affecting health behavior that influences chronic disease, non-Hispanic Black women with diabetes reported that experienced racism led to maladaptive coping strategies which included unhealthy food choices and that these choices affected diabetes self-management ( 91 , 110 ). Lastly, interventions should certainly incorporate the element of hope, as hope, optimism, and happiness are essential components to human health and have been shown to be accompanied by decreasing IL-6 levels ( 111 , 112 ). This might seem like a list of unbreakable, vicious cycles pre-dispositioning vulnerable populations to COVID-19.…”
Section: Behavioral Interventions Impacting Il-6 Levels and The Immunmentioning
confidence: 99%